Assessment of nanoparticle loading and dispersion in polymeric materials using oscillatory photon correlation spectroscopy. (February 2016) - Broughton, W.R.; Koukoulas, T.; Woolliams, P.
Abstract: The inclusion of small concentrations of nanoparticles in polymeric materials (≤5 wt. %) can significantly enhance material properties and functionality. However, poor or non-uniform particle dispersion resulting in particle clustering (agglomeration) in polymer nanocomposites (PNCs) limits the potential for property enhancement in these materials. Achieving good dispersion is considered essential for successful commercialization of PNCs. Hence, reliable and accurate measurement techniques for characterizing particle loading and dispersion would significantly contribute towards understanding and optimizing the material performance of PNCs, and consequently play a pivotal role in product development. This paper, the last of three papers on optical techniques, presents the results of a study using a dynamic light scattering technique, oscillatory photon correlation spectroscopy (Os-PCS), for discriminating between different particle loadings and levels of dispersion. The technique has been applied to two epoxy-based resin systems reinforced with either nanoclay platelets or silica microspheres.